Pembelajaran Pendidikan Agama Islam Berbasis Kearifan Dayak di SMPN 1 Palangka Raya - Muhajir, Ahmad; Muslimah, Muslimah (Paedagogie: Jurnal Pendidikan dan Studi Islam, 2025)
This study aims to analyze Islamic Religious Education (PAI) learning based on Dayak wisdom at SMPN 1 Palangka Raya . Local wisdom values, such as mutual cooperation, deliberation, and harmony with nature, are implemented in PAI learning to strengthen students’ understanding of Islamic teachings while fostering tolerance in a multicultural society. This research uses a qualitative approach. Data were collected through participant observation of Dayak culture-based learning, in-depth interviews with teachers as research subjects, as well as with the principal and 17 students as research informants, and documentation analysis. The results show that integrating Dayak local wisdom into PAI learning at SMPN 1 Palangka Raya not only enhances students’ understanding of religious values but also shapes better tolerance attitudes. Students become more open-minded and appreciative of cultural and religious differences among their classmates. This Dayak local wisdom-based learning has also proven effective in fostering harmony and peace within the school environment.